Mobile testing : an ASTQB-BCS foundation guide - Black, Rex, 1964- (BCS, the Chartered Institute for IT, 2018)
Mobile testing is the process of testing the functionality, usability and consistency of mobile software. With this essential guide, in line with the ASTQB Certified Mobile Tester syllabus, you will gain the understanding and skills you require to begin your journey to becoming a proficient mobile tester. Mobile testing is the process of testing the functionality, usability and consistency of mobile software. While similar to standard software testing, efficient and effective mobile testing requires an additional set of skills on top of those usually required by software testers. With this essential guide, in line with the ASTQB Certified Mobile Tester syllabus, you will gain the understanding and skills you require to begin your journey to becoming a proficient mobile tester.
Includes index.
Keywords: Mobile apps -- Testing.; Mobile computing.; Computer software -- Testing.; elektronické knihy; electronic books